A variant fisher and Jaikuamr algorithm to solve capacitated vehicle routing problem - Sultana, Tanzima; Akhand, Md Aminul Haque; Rahman, M.M. Hafizur (IEEE, 2017)
Vehicle Routing Problem (VRP) is a real life constraint satisfaction problem to find minimal travel distances of vehicles to serve customers. Capacitated CVRP (CVRP) is the simplest form of VRP considering vehicle capacity constraint. Constructive and clustering are the two popular approaches to solve CVRP. A constructive approach creates routes and attempts to minimize the cost at the same time. On the other hand, a clustering based method first assigns nodes into vehicle wise cluster and then generates route for each vehicle. Route generation is a traveling sales man problem (TSP) and any TSP optimization method is useful for this purpose. Fisher and Jaikumar algorithm is a well-known cluster based method which creates clusters with a geometric method partitioning the customer plane into equal angular cones where the total cones are equal to the number of vehicles. This study investigates a variant of Fisher and Jaikumar algorithm owning to solve CVRP efficiently. In the proposed method clusters form such a way that each cluster cone contains equal number of nodes. The initial clusters formation in a method are subjected to route optimization. Three prominent metaheuristic methods (i.e., genetic algorithm, ant colony optimization, particle swarm optimization) for TSP are considered for route optimization. The efficiency of the proposed method is identified while solving benchmark CVRPs. Experimental result reveals that variant Fisher and Jaikumar with particle swarm optimization is an effective method in solving CVRP.